1998
DOI: 10.1097/00007890-199801270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus (Fk506) and Mycophenolate Mofetil Combination Therapy Versus Tacrolimus in Adult Liver Transplantation1

Abstract: Combination therapy with tacrolimus and MMF may significantly reduce the incidence of acute liver allograft rejection, allow a significant reduction in tacrolimus dosage, and decrease the incidence of nephrotoxicity. Long-term analysis will be necessary to assess any increased risk of opportunistic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 39 publications
8
58
0
1
Order By: Relevance
“…21 In the setting of OLT, the use of MMF seems to allow a reduction in cyclosporine or tacrolimus dose and therefore decreased toxicity. 22 In this report, the use of MMF allowed us to reduce the dose of cyclosporine, even achieving complete withdrawal in most patients. Cyclosporine withdrawal was followed by a moderate but significant improvement in renal function, with a decrease in serum creatinine and urea levels of 0.35 Ϯ 0.14 mg/dL and 0.35 Ϯ 0.04 g/L, respectively, and an increase in creatinine clearance of 8.86 Ϯ 2.08 mL/min.…”
Section: Discussionmentioning
confidence: 85%
“…21 In the setting of OLT, the use of MMF seems to allow a reduction in cyclosporine or tacrolimus dose and therefore decreased toxicity. 22 In this report, the use of MMF allowed us to reduce the dose of cyclosporine, even achieving complete withdrawal in most patients. Cyclosporine withdrawal was followed by a moderate but significant improvement in renal function, with a decrease in serum creatinine and urea levels of 0.35 Ϯ 0.14 mg/dL and 0.35 Ϯ 0.04 g/L, respectively, and an increase in creatinine clearance of 8.86 Ϯ 2.08 mL/min.…”
Section: Discussionmentioning
confidence: 85%
“…Eckhoff et al [34] performed a study of liver transplantation, in which there were similar rates of CMV infection among patients receiving tacrolimus versus tacrolimus plus 2g MMF. Lastly, a randomized multicentric trial of 2g MMF versus azathioprine treatment of lung transplant recipients [35] revealed similar rates of CMV infection.…”
Section: Risk Of Cytomegalovirus Infection In Transplant Recipientsmentioning
confidence: 99%
“…The success of OLT has improved dramatically over the past few decades [2]. An important aspect of this success is the availability of more potent immunosuppressive drugs.…”
Section: Introductionmentioning
confidence: 99%